If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + y = 43 Solving 3x + y = 43 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 3x + y + -1y = 43 + -1y Combine like terms: y + -1y = 0 3x + 0 = 43 + -1y 3x = 43 + -1y Divide each side by '3'. x = 14.33333333 + -0.3333333333y Simplifying x = 14.33333333 + -0.3333333333y
| x9/2 | | (1+4x)-x(3-2x)= | | 5x-23/6=x-4 | | 12y-6y^2=0 | | 3x+3+2x-2+9x=180 | | 2(-2.2)-9(2(2.2)+5)=7(2(2.2)+3) | | 2x+2y-7y-4x=a | | -6-1/3w=0 | | 2(x-3)-4(3x-2)=12 | | 6x+2-11x=9-4x+2 | | 7x^4+6=y^2 | | 6(7x-4)=144 | | 18.75=0.3xtloge | | 6g+7=-5 | | 3a+8b+7a-6b= | | X11/5 | | 6y(6-y)=0 | | 3am+8b+7a-6b= | | x(20-2x)=0 | | 4(3w-2)= | | 8x(-152+x)=-96 | | 5(4x+7)=95 | | 5(4x-9)=3x | | 2x-2+9x=3x+3 | | (8x-40)/(x^2-81) | | 2(1-3x)=4-2(3x+7) | | 1/6-4/5 | | 2x-2=9x | | 1/5(3y-4)=2/5 | | x^2-10z+7=0 | | 9y=7(y-8) | | 3(b+2)-b=8b-18 |